Clinical Features, Diagnosis, Management and Prognosis of Primary Intraocular Lymphoma - Chen, Youxin; Zhao, Xinyu; Cheng, Tiantian; Meng, Lihui; Zhang, Wenfei (Frontiers in Oncology, 2022)
Purpose To evaluate the clinical features, diagnostic techniques, various treatment strategies and prognosis of primary intraocular lymphoma (PIOL). Methods The databases PubMed, EMBASE, and Ovid were searched from inception to March 2021 to identify relevant studies. Statistical analyses were performed with R version 3.3.1. Results 87 studies involving 1484 patients (aged from 14 to 90 years old) were finally included. The pooling results indicated PIOL patients were female, elderly, binocular and B cell type dominated. About 19% have central nervous system (CNS) involvement at the first visit. During follow-up, the incidence of CNS involvement, death rate, 2-year and 5-year survival rate, 1-year and 2-year progression-free survival, and recurrence rate were 58%, 33%, 82%, 70%, 88%, 70%, 44%, respectively. The most common recurrent site was CNS. The delayed diagnosis rate was 85%, the misdiagnosed rate was 64%. The diagnostic technique with the highest positive rate was IL10:IL6>1 of aqueous (98%). The most common symptoms, signs, FFA and OCT features were blurring of vision (72%), vitreous inflammatory opacity (92%), FA/FAF reversal (91%) and hyper-reflective foci in posterior vitreous (53%), respectively. The prognosis of PIOL patients without CNS involvement was obviously better than those with CNS involvement. Overall, intravitreal injection of chemotherapy drug plus systemic chemotherapy (IV+CT) could achieve satisfactory prognosis, the combination of local radiotherapy (RT) could further decrease the recurrent and death rate. Conclusion PIOL patients with CNS involvement had significantly worse prognosis. The aqueous humor examination should be regarded as first-line and routine diagnostic technique. IV+CT could achieve satisfactory prognosis, the combination of RT was also beneficial.